“Men of their House”: Memories of the Rural Unionization in Northeastern Brazil during the 1960s (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article is based in a fieldwork conducted in the lands of a large rural property, now defunct, located in northeastern Brazil. I explore the reconstructions of ancient locals about their experiences of unionization, before and after the mi- litary coup in 1964. I would like to demonstrate how these reconstructions show complex experiences that intertwined moral values – for instance, to be a “man of the house”, not a “thief” -, circuits of reciprocity, neighborhood and family relationships, and the construction of new rights and institutional positions in a larger scale. I understand these experiences involve an analytical effort to weave elements that are often separated by other social studies.
Keywords: Rural Unionization; Rio Grande do Norte; Memory.